Glasbena ustvarjalnost in poustvarjalnost na Slovenskem v 20. stoletju - Stefanija, Leon (De musica disserenda, 2010)
This paper provides an overview of the literature on Slovenian musical composition and performance. The text is devided into three parts, the first two dealing with more comprehensive historical monographs and partial studies of individual musicians and phenomena. The final section offers a look at what seems to be the main difficulty with respect to twentieth-century Slovenian music historiography - the vaguely worked out relations between musical composition, performance, and reception - and concludes with a suggestion for further work centered around the following four historiographical topoi: 1) analysis of the functions and perception of music, 2) analysis of music institutions, 3) monographs on musicians and musical phenomena, and 4) integrating various genres and styles into the historical perspectives.
Keywords: slovenska glasba; zgodovina glasbe; 20.st.; muzikologija; Slovenia; Slovenija